Revizyon stapes cerrahisi - (:unkn) unknown (My University, 2000)
Amaç: Revizyon stapedotomi uygulanan olguları, revizyon nedenlerini ve revizyon sonrası sonuçları değerlendirmek. Hastalar ve Yöntemler: Revizyon stapes cerrahisi uygulanan 23 olgu (18 kadın, 5 erkek; ort. yaş 40.4; yaş dağılımı 17-58) retrospektif olarak incelendi. Revizyon öncesi başvuru nedenleri iki olguda (%8.6) baş dönmesi, bir olguda (%4.3) çınlama ve 20 olguda (%86.9) işitme kaybı idi. Uygulanan ilk cerrahi ile revizyon arasındaki süre 10 gün ile 48 ay arasında değişmekteydi. Revizyon nedenleri ve işitme sonuçları değerlendirildi. Bulgular: Protez çevresi yapışıklıklar, inkus nekrozu, granülom en sık rastlanan revizyon nedenleri olarak belirlendi. İşitmede düzelme oranı (hava-kemik aralığı <10 dB) %43.4 olarak saptandı. Sonuç: Revizyon stapes cerrahisi teknik olarak daha zordur ve optimal postoperatif işitme sonuçları daha düşük oranda elde edilmektedir.

Objectives: To evaluate patients who underwent revision stapedotomy, together with its indications and results. Patients and Methods: The study included 23 patients (18 females, 5 males; mean age 40.4 years; range 17-58 years) who underwent revision stapes surgery. Before revision, the patients presented with dizziness (n=2, 8.6%), tinnitus (n=1, 4.3%), and hearing loss (n=20, 86.9%). The interval between the first operation and the revision ranged between 10 days and 48 months. Reasons for revision and hearing results were evaluated. Results: The most common causes for revision were fibrotic adhesions to prosthesis, incus necrosis, and granuloma. Hearing improvement (air-bone gap <10 dB) was 43.4% after revision stapes surgery. Conclusion: Technically, revision stapes surgery is more challenging, with less postoperative hearing improvement.
Revision stapes surgery
Keywords: Anestezi; Odyoloji ve Konuşma-Dil Patolojisi; Ortopedi; Kulak, Burun, Boğaz; Radyoloji, Nükleer Tıp, Tıbbi Görüntüleme; Cerrahi